1999
DOI: 10.1046/j.1439-0388.1999.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variation between an African and five European taurine breeds results in a geographical phylogenetic tree with a bison outgroup

Abstract: Introduction Genetic variation is being used extensively for individual identification and linkage analysis, and may be useful for interpopulation studies. Previously, blood groups and biochemical variants in blood cell and serum proteins have been used to study (evolutionary) relationships in mammals. But genetic divergence and gene flow among closely related populations are difficult to measure with these classical markers because their mutation rate is so low that new mutations have not had sufficient time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
2
9
1
1
Order By: Relevance
“…The moderate F ST values implied that the majority of total allelic variation (93.5%) corresponds to differences among individuals, and only 6.5% of the total genetic variation could be attributed to differences among breeds. The genetic differentiation observed for the two Indian breeds is somewhat higher than that reported for seven European cattle breeds (0.1%) by MacHugh et al (1998) and lower than that reported for Belgian cattle (3.5%; Mommens et al 1999). The number of migrants per generation (N m ) was observed to be 3.62, which perhaps has not influenced the diffusion of genetic structure of the two cattle breeds.…”
Section: Genetic Differentiation and Population Structurecontrasting
confidence: 72%
“…The moderate F ST values implied that the majority of total allelic variation (93.5%) corresponds to differences among individuals, and only 6.5% of the total genetic variation could be attributed to differences among breeds. The genetic differentiation observed for the two Indian breeds is somewhat higher than that reported for seven European cattle breeds (0.1%) by MacHugh et al (1998) and lower than that reported for Belgian cattle (3.5%; Mommens et al 1999). The number of migrants per generation (N m ) was observed to be 3.62, which perhaps has not influenced the diffusion of genetic structure of the two cattle breeds.…”
Section: Genetic Differentiation and Population Structurecontrasting
confidence: 72%
“…This value for within breed variation is similar to other findings for this breed (Ndumu et al, 2008b), and quite high when compared to the 6% between 12 African cattle breeds of Cameroon and Nigeria (Ibeagha-Awemu and Erhardt, 2006). The level of differentiation was also much higher than 2.6% found between three populations of the Spanish Alberes cattle breed (Casellas et al, 2004) and 3.5% found between Belgian cattle populations (Mommens et al, 1999). This could be explained by differences in population history and management.…”
Section: Genetic Differentiation Among Ankole Cattle Populationsmentioning
confidence: 67%
“…We have found similar close relationships between black and white populations, and between Polish and German Red breeds. Mommens et al (1999) evaluated the relationship of five Belgian breeds and African N'Dama by means of microsatellites. American bison served as an outgroup.…”
Section: Resultsmentioning
confidence: 99%